2023
DOI: 10.15376/biores.18.3.5750-5764
|View full text |Cite
|
Sign up to set email alerts
|

Interface design for the mobile terminal for furniture shopping in the post-epidemic era: An empirical evidence of user demand collection

Abstract: The Internet economy is flourishing, and the form of consumption has shifted from offline brick-and-mortar shopping to online consumption. At the same time, COVID-19 led to many offline stores being constrained in many ways, accelerating the conversion of shopping. The purpose of the study is to enable users to effectively use mobile products and optimize their service experience during furniture consumption. This study compares the relevant theories and the current state of research. Through qualitative and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This paper establishes that perceived consumer effectiveness (PCE) has a positive impact on the intention to purchase green furniture by increasing arousal level (β = 0.085, p < 0.001). Zhang et al (2023) [85] confirmed that the aesthetic design layout of the product detail page influences consumers' purchase intentions. This study also confirmed that aesthetic design (AD) increases consumers' desire to purchase by positively impacting the level of perceived enjoyment (β = 0.064, p < 0.001).…”
Section: Discussionmentioning
confidence: 69%
“…This paper establishes that perceived consumer effectiveness (PCE) has a positive impact on the intention to purchase green furniture by increasing arousal level (β = 0.085, p < 0.001). Zhang et al (2023) [85] confirmed that the aesthetic design layout of the product detail page influences consumers' purchase intentions. This study also confirmed that aesthetic design (AD) increases consumers' desire to purchase by positively impacting the level of perceived enjoyment (β = 0.064, p < 0.001).…”
Section: Discussionmentioning
confidence: 69%